2008
DOI: 10.1111/j.1538-7836.2007.02837.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcome in patients with venous thromboembolism and hidden cancer: findings from the RIETE Registry

Abstract: To cite this article: Trujillo-Santos J, Prandoni P, Rivron-Guillot K, Romá n P, Sá nchez R, Tiberio G, Monreal M, the RIETE Investigators. Clinical outcome in patients with venous thromboembolism and hidden cancer: findings from the RIETE Registry. J Thromb Haemost 2008; 6: 251-5.See also Sørensen HT, Johnsen SP. Venous thromboembolism and subsequent short-term risk of an occult cancer. This issue, pp 249-50.Summary. Introduction: Although extensive screening in patients with venous thromboembolism (VTE) may … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
20
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 22 publications
(23 reference statements)
2
20
2
Order By: Relevance
“…Our findings are consistent with a retrospective study reporting an independent association between an elevated WBC count (>11.0 3 10 9 /L) and 30-day mortality in 150 patients with PE [19]. Similarly, data from the RIETE registry showed that an elevated WBC is significantly associated with adverse outcomes in patients with acute venous thromboembolism who have cancer [24].…”
Section: Discussionsupporting
confidence: 81%
“…Our findings are consistent with a retrospective study reporting an independent association between an elevated WBC count (>11.0 3 10 9 /L) and 30-day mortality in 150 patients with PE [19]. Similarly, data from the RIETE registry showed that an elevated WBC is significantly associated with adverse outcomes in patients with acute venous thromboembolism who have cancer [24].…”
Section: Discussionsupporting
confidence: 81%
“…As we did not find any differences between men and women either, both genders should be screened to the same extent. Earlier studies have indicated that the location of the thrombosis has a bearing on the the probability of underlying malignancy (22,23) and that certain types of cancer are more strongly associated with venous thromboembolism than others (4,21,24). We found no evidence of this in our material.…”
Section: Discussioncontrasting
confidence: 56%
“…In contrast to the findings of a number of other studies, we found no difference in age distribution between those who developed cancer during the first year and those who did not. This indicates that malignancy screening should not only be carried out for the over 60s age group, as some have proposed (6,21,22). As we did not find any differences between men and women either, both genders should be screened to the same extent.…”
Section: Discussionmentioning
confidence: 99%
“…7 In the Registro Informatizado de la Enfermedad Trombo-Embólica (RIETE) registry that included 3805 cancer patients with acute VTE, those with leukocytosis had a 1.6-fold increased risk of recurrent VTE. 8 The exact causative role of leukocytosis in cancer-related VTE remains to be elucidated. It was shown that tumors release inflammatory cytokines into the circulation that activate tissue factor expressed on monocytes and endothelial cells.…”
Section: Potential Predictive Biomarkers Blood Count Parametersmentioning
confidence: 99%